PERAMALAN PENJUALAN KAIN BATIK PADA PENJAHIT RUSLAN MENGGUNAKAN METODE AUTOREGRESSIVE INTEGRATED MOVING AVERAGE (ARIMA) - Afrijal, Afrijal; Sabri, Khairul (JURNAL ECONOMICA: Media Komunikasi ISEI Riau, 2024)
Batik cloth is one of the textile products that plays an important role in Indonesian culture and has received international recognition as a unique and valuable traditional art. Ruslan Tailor is one of the business actors in the sale of batik cloth operating in Indonesia. Therefore, Ruslan Tailor needs to understand past sales trends and plan inventory more efficiently. forecasting has been proven effective in predicting product sales with trends and seasonal patterns. By applying the ARIMA method to batik cloth sales data, Ruslan Tailor can identify sales patterns, trends, and seasonal variability, which in turn will help in making better decisions related to inventory management, production planning, and marketing. The results of this study show that the level of accuracy of Ruslan Tailor's batik cloth forecasting is 96%. Thus, this study will not only help Ruslan Tailor in improving its operational efficiency, but can also provide valuable guidance for other batik cloth business actors. Keywords: Forecasting, Sales, Batik, Tailor Ruslan